Sequential tests of multiple hypotheses controlling false discovery and nondiscovery rates. Issue 1 (2nd January 2020) - Bartroff, Jay; Song, Jinlin
Abstract: We propose a general and flexible procedure for testing multiple hypotheses about sequential (or streaming) data that simultaneously controls both the false discovery rate (FDR) and false nondiscovery rate (FNR) under minimal assumptions about the data streams, which may differ in distribution and dimension and be dependent. All that is needed is a test statistic for each data stream that controls its conventional type I and II error probabilities, and no information or assumptions are required about the joint distribution of the statistics or data streams. The procedure can be used with sequential, group sequential, truncated, or other sampling schemes. The procedure is a natural extension of Benjamini and Hochberg's (1995 ) widely used fixed sample size procedure to the domain of sequential data, with the added benefit of simultaneous FDR and FNR control that sequential sampling affords. We prove the procedure's error control and give some tips for implementation in commonly encountered testing situations.